ANALYSIS OF THE READINESS OF MSMEs ACTORS IN THE IMPLEMENTATION OF SAK EMKM IN PURWOKERTO - Riyan Ardiana; Bambang Setyobudi Irianto; Kiky Srirejeki (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2019)
This study aims to analyze the influence of attitude, subjective norms, perceived behavioral control, and awareness on the intentions of MSMEs actors in the readiness of MSMEs actors in the implementation of SAK EMKM. The population in this study was all MSMEs in Purwokerto. This study used Theory of Planned Behavior with the addition of one variable, namely awareness. The research data was obtained directly from respondents through a questionnaire with disproportionate stratified random sampling technique and quantitative approaches of Partial Least Square (PLS). The results of this research indicate that the attitude and perceived behavioral control significantly influence the intention of MSMEs actors in the implementation of SAK EMKM. Subjective norms and awareness did not significantly influence the intention of MSMEs actors in the implementation of SAK EMKM. Intention significantly influence on the readiness of MSMEs actors in the implementation of SAK EMKM.